Usefulness of interferon-γ release assay for the diagnosis of sputum smear-negative pulmonary and extra-pulmonary TB in Zhejiang Province, China - Lei Ji; Yong-Liang Lou; Zhong-Xiu Wu; Jin-Qin Jiang; Xing-Li Fan; Li-Fang Wang; Xiao-Xiang Liu; Peng Du; Jie Yan; Ai-Hua Sun (BMC, 2017)
Abstract Background Quick diagnosis of smear-negative pulmonary tuberculosis (TB) and extra-pulmonary TB are urgently needed in clinical diagnosis. Our research aims to investigate the usefulness of the interferon-γ release assay (IGRA) for the diagnosis of smear-negative pulmonary and extra-pulmonary TB. Methods We performed TB antibody and TB-IGRA tests on 389 pulmonary TB patients (including 120 smear-positive pulmonary TB patients and 269 smear-negative pulmonary TB patients), 113 extra-pulmonary TB patients, 81 patients with other pulmonary diseases and 100 healthy controls. Blood samples for the TB-Ab test and the TB-IGRA were collected, processed, and interpreted according to the manufacturer's protocol. Results The detection ratio of smear-positive pulmonary TB patients and smear-negative pulmonary TB patients were 90.8% (109 of 120) and 89.6% (241 of 269), respectively. There was no statistically significant difference of its performance between these two sample sets (P > 0.05). The detection ratio of positive TB patients and extra-pulmonary TB patients were 90.0% (350 of 389) and 87.6% (99 of 113), respectively, which was not significantly different (P > 0.05). Conclusions In this work, the total detection ratio using TB-IGRA was 89.4%, therefore TB-IGRA has diagnostic values in smear-negative pulmonary TB and extra-pulmonary TB diagnosis.